Do athlete and coach performance perfectionism predict athlete burnout? - Olsson, L. F.; Madigan, D. J.; Hill, A. P.; Grugan, M. C. (European Journal of Sport Science, 2022)
Research has illustrated that athlete perfectionism predicts athlete burnout. The present study sought to build on existing research in two ways. First, we provide the first test of the relationship between performance perfectionism and athlete burnout. That is, whether the degree to which athlete`s expect their own or others` sport performances to be perfect, predicts burnout. Second, we broaden the examination of the perfectionism-burnout relationship to include coaches by testing the incremental predictive ability of perceptions of coach other-oriented performance perfectionism (the degree to which coaches were perceived to expect perfect performances from others). A sample of 190 competitive adult athletes (M age = 20.54) completed measures of their own performance perfectionism (self-oriented, socially prescribed, and other-oriented performance perfectionism), perceived coach other-oriented performance perfectionism, and burnout symptoms. Regression analyses indicated that both athlete self-oriented and socially prescribed performance perfectionism positively predicted athlete burnout. In addition, after controlling for all dimensions of athlete performance perfectionism, perceived coach other-oriented performance perfectionism positively predicted athlete burnout. The findings suggest that, in addition to their own perfectionism, when athletes perceive their coaches to be more perfectionistic towards others, they are more likely to experience burnout.